Assessment of irrigation performance along the canal reach of community managed scheme in southern Ethiopia - Bantero, B.; Ayana, M.; Awulachew, Seleshi Bekele (2010)
This paper presents the results of irrigation performance assessment made along the canal reaches of community-managed Hare irrigation scheme in Southern Ethiopia. Field measurement, interview, group discussion and measurement of water supply were undertaken, and output performance indicators were assessed. Measurements of cropping intensity, irrigation interval and productivity show that there is a distinct difference in performance along the main canal. Upstream water users always have easy access to water, higher annual income and resource base than those in midstream and downstream. Disparity among users occurs due to lack of functional institutions and poor conditions of water distribution systems.